2016
DOI: 10.1002/cyto.b.21357
|View full text |Cite
|
Sign up to set email alerts
|

Small, abnormal B lymphoid blast populations in chronic myelogenous leukemia at diagnosis: Does this finding indicate an accelerated course?

Abstract: Immature B cells, occasionally including a small subset with an abnormal phenotype can be observed in chronic phase CML at diagnosis. We believe an approach incorporating clinical data, cytogenetic/molecular findings, and morphologic evaluation may be helpful when determining the best management of CML patients at diagnosis if small ABLB populations are identified by FC. © 2016 Clinical Cytometry Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 13 publications
(30 reference statements)
1
15
0
Order By: Relevance
“…However, Vrotsos and colleagues found abnormal precursor B cell populations in 4 of 36 adult CML‐CP patients in the diagnostic marrow samples, and the 3 patients with median 38 months follow‐up (range 17–46 months) achieved and maintained a deep or MMR with TKI therapy (Vrotsos et al, 2017). Soma et al (2016) also reported the detection of a small population of abnormal lymphoblasts by FCM in 6 of their CML‐CP patients (5/6 adults, 1/6 child) and at a median follow up of 32 months (range 4–67 months), none had progressive blast phase on TKI therapy. Here we report that three out of five (60%) children with CML‐CP with measurable ALB at baseline by multicolor flow‐cytometry had sudden onset blast crisis on TKI therapy, results similar to that of Rassi et al We also demonstrated that the low‐level ABLB present at CML‐CP express remarkably similar immunophenotypic profile, and they exhibited similar phenotype at the time of blast crisis suggesting continuity.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, Vrotsos and colleagues found abnormal precursor B cell populations in 4 of 36 adult CML‐CP patients in the diagnostic marrow samples, and the 3 patients with median 38 months follow‐up (range 17–46 months) achieved and maintained a deep or MMR with TKI therapy (Vrotsos et al, 2017). Soma et al (2016) also reported the detection of a small population of abnormal lymphoblasts by FCM in 6 of their CML‐CP patients (5/6 adults, 1/6 child) and at a median follow up of 32 months (range 4–67 months), none had progressive blast phase on TKI therapy. Here we report that three out of five (60%) children with CML‐CP with measurable ALB at baseline by multicolor flow‐cytometry had sudden onset blast crisis on TKI therapy, results similar to that of Rassi et al We also demonstrated that the low‐level ABLB present at CML‐CP express remarkably similar immunophenotypic profile, and they exhibited similar phenotype at the time of blast crisis suggesting continuity.…”
Section: Discussionmentioning
confidence: 94%
“…There are no prospective studies that have specifically looked into the incidence and significance of aberrant blasts detected by FCM in CML‐CP. Also, the literature on the significance of measurable <10% abnormal lymphoid blasts (ALB) at diagnosis in pediatric CML‐CP patients as a marker of early progression is scarce and conflicting (Derderian et al, 1993; El Rassi et al, 2015; Soma, Oehler, Ding, & Cherian, 2016; Vrotsos, Gorgan, & DiGiuseppe, 2017). We looked specifically into the profile and outcomes of pediatric CML‐CP patients with abnormal FCM findings at baseline.…”
Section: Introductionmentioning
confidence: 99%
“…The authors conclude CD13, CD10, and CD38 co‐expression is the most predictive immunophenotype of BCR/ABL1 translocation in acute B lymphoblastic leukemia. In addition to their prognostic significance, these data will help define highly informative antigens for standardization and regulatory requirements .…”
Section: Malignant Hematologymentioning
confidence: 99%
“…However a circumstance that might require caution is the identification of very rare B‐lymphoblasts in the setting of CML. Although the latter finding is very worrisome for blasts crisis, there have been reports of patients with CML with rare bone marrow B lymphoblasts identified by flow cytometry who do not develop progressive disease . Therefore, bone marrow examination is probably warranted.…”
Section: Complete Blood Cell Count and Peripheral Smear Review Findingsmentioning
confidence: 99%